Analysis of management performance index and user satisfaction index in Kutaraja Fishing Port, Banda Aceh, Indonesia. Issue 1 (February 2021) - Chaliluddin, M A; Pratiwi, A; Rizwan, T; Kandi, O
Abstract: The problems faced by managers and being felt by fishing port users today are the problem of environmental cleanliness and the lack of fishin port management efforts in serving fishermen's needs, this is due to the government's lack of attention in implementing the functions and roles of fishing ports and existing facilities. This study aims to determine the level of performance of the Kutaraja fishing port management and the level of user satisfaction regarding the services of the Kutaraja fishing port. This research was conducted in February 2020. Located at the Kutaraja fishing port. The research method used is the survey method, namely by observing and collecting data directly on the performance of the Kutaraja fishing port management and user satisfaction regarding the services of the Kutaraja fishing port. Data collection was carried out by interview assisted by a linsit of questions / questionnaires. The results showed that the percentage value of the fishing port performance index was 78.2%. This value shows that the performance of the Kutaraja fishing port is already at a good level. The user decision index value obtained is 94.02%. This shows that the Kutaraja fishing port is still lacking in the provision of facilities, the utilization of the facilities is still low and the management of the facilities does not reflect that overall users are very satisfied with the service performance of Kutaraja fishing port, Banda Aceh, Indonesia.